Answers

2014-03-13T23:31:37+05:30
This kind of calculation should follow a rule

First you have calculate values in brackets, next division then multiplication, after multiplication, addition finally subtraction.

In this case, [-2*4+5-3 (-2)*(-2)+5*2]
=[-2*4+5-(-6)*(-2)+5*2] (multiply 3 with -2)
=[-2*4+5-12+5*2] (multiply 6 with -2)
=[-8+5-12+10] (multiply -2 with 4 and 5 with 2)
=[-3-2]
=-5
0
2014-03-14T11:54:16+05:30
-2*4=-8
so
-8+5=-3
-3*4=-12
so
-3-12=-15
now 5*2=10
so
-15+10=5
s0
-8+5-12+10=-5
0